1998
DOI: 10.1002/(sici)1096-9136(1998120)15:12<1022::aid-dia720>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Rapid gastric emptying of a liquid meal in long-term Type 2 diabetes mellitus

Abstract: Both delayed and accelerated gastric emptying rate (GER) have been reported in patients with diabetes mellitus. Delayed GER has been attributed to autonomic neuropathy in established diabetes but rapid GER was demonstrated in early Type 2 diabetes. The aim of the study was to investigate rapid gastric emptying in a group of people with long-duration Type 2 diabetes. GER of a radiolabelled liquid meal was studied scintigraphically in 20 Type 2 patients with a mean (+/-SEM) duration of diabetes 13 (+/-1) years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
17
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 21 publications
5
17
0
1
Order By: Relevance
“…In direct contrast to the results from Frank et al [47], they found no difference between liquid and solid-phase emptying but did find a significant difference in half-emptying time of the solid meal, and rapid emptying was more common among the diabetic group. Weytjens et al [49] assessed gastric emptying in patients with long-term T2DM (mean duration of diabetes, 13 years); 70% of the patients in the diabetic group had accelerated gastric emptying of a liquid meal.…”
Section: Rapid Gastric Emptying In Td2mmentioning
confidence: 99%
“…In direct contrast to the results from Frank et al [47], they found no difference between liquid and solid-phase emptying but did find a significant difference in half-emptying time of the solid meal, and rapid emptying was more common among the diabetic group. Weytjens et al [49] assessed gastric emptying in patients with long-term T2DM (mean duration of diabetes, 13 years); 70% of the patients in the diabetic group had accelerated gastric emptying of a liquid meal.…”
Section: Rapid Gastric Emptying In Td2mmentioning
confidence: 99%
“…Delayed GET has been attributed to autonomic neuropathy in established diabetes, but rapid GET was demonstrated in early type II diabetes [27,28]. Patients with recent onset diabetes mellitus may exhibit accelerated GET of liquids and solids that has not been correlated to neuronal dysfunction but, rather, increased phasic motor activity in the gastric fundus in these patients, suggesting a motor abnormality in this region [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that rapid gastric emptying of high-carbohydrate and liquid nutrient meals is common in patients with type 2 diabetes, particularly those who show no signs of autonomic neuropathy. 12,13,17 In a study in which a dual-labeled meal was administered to patients with type 2 diabetes and control subjects, the patients with type 2 diabetes had rapid gastric emptying of the 50-g liquid carbohydrate component of the dual-labeled solid and liquid meal (65 minutes half emptying time in patients with type 2 diabetes vs Clinical Nuclear Medicine • Volume 32, Number 3, March 2007 Rapid and Delayed Gastric Emptying 103 minutes half emptying time in controls) while having a normal emptying time of a radiolabeled solid meal component. 18 In this study, anterior imaging alone was used without an additional posterior image for calculation of the geometric mean.…”
Section: Santiago-maldonado and Phillipsmentioning
confidence: 99%
“…Rapid gastric emptying has been more commonly reported when all of the components of a solid meal were labeled with a radiotracer 1 or in meals composed of liquids or semisolids such as mashed potatoes in which the radiotracer is homogeneously dispersed throughout the whole meal. 2,5,12 These meals are very different than egg-based meals in which the egg is labeled but the majority of the meal nutrient content is unlabeled, ie, the bread and jam. The most commonly used meal for scintigraphic gastric emptying imaging studies in the United States is an egg-based solid meal in which the majority of the caloric content of the meal is administered as unlabeled bread and jam in addition of radiolabeled eggs.…”
mentioning
confidence: 99%